Efeito imediato e tardio da estimulação elétrica nervosa transcutânea aplicada durante o exercício resistido na intensidade de dor e no desempenho físico de indivíduos saudáveis : ensaio clínico randomizado - Menezes, Mayara Alves (2018)
Introduction: Exercise-induced muscle pain is a self-limiting condition and may have an impact on the physical activity habits of healthy individuals, patients with musculoskeletal pain and athletes. Strategies for the management of muscle pain are solely focused on controlling the symptoms after the muscle injury is already stablished. Transcutaneous Electrical Nerve Stimulation (TENS) has shown positive results for pain reduction and functional improvement in acute and chronic pain conditions. Thus, we propose that applying TENS during exercise might reduce pain and contribute to higher adherence to physical activity and better physical performance. Aim: Investigate the immediate and long-term effects of TENS applied during resisted exercise on pain intensity and physical performance of healthy subjects. Methods: This study is a randomized, double-blinded, placebo-controlled, clinical trial. The sample consists of 46 college students, of both sexes, healthy, irregularly active or sedentary, aged between 18 and 40 years. Subjects were randomly assigned into two groups: active (24) or placebo (22) TENS. The study was conducted over 5 moments: on day 1, subjects performed the one-repetition maximum test (1RM); 72 hours later, on day 2, 1RM was retested; 48 hour later, on day 3, TENS was applied during a functional resisted exercise protocol for upper limbs (bench press and rowing), with an intensity of 80% of 1RM; and 24h after, on day 4, the subjects were reevaluated. Assessment included pain intensity at rest and with movement, pressure pain threshold, temporal summation, conditioned pain modulation, infrared thermography, cardiorespiratory measures, functionality, muscle fatigue, number exercise of repetitions, muscle potency and physical tolerance. Pain measures and TENS application was on the muscle belly of the pectoralis major and latissimus dorsi. Results: TENS did not reduce pain intensity when compared to placebo (p>0.05). Active TENS increased pressure pain threshold in latissimus dorsi: p=0.02 and anterior tibial p=0.04 at the immediate reassessment. Immediate effects of TENS were significant for fatigue perception at rest (p=0.01) and with movement was similar to placebo (p<0.05). A higher number of exercise repetitions were observed in the active TENS group, starting from the 5º set of the rowing exercise (p=0.002). Reduction on physical performance was observed, with no differences between groups (p<0.05). Conclusion: Our results show that TENS did not alter pain perception in healthy individuals, but its use induced increased muscle action, contributing to a greater fatigue perception.